TELAAH PEMIKIRAN ISLAM LIBERAL DALAM NOVEL “KEMI” KARYA ADIAN HUSAINI PERSPEKTIF PENDIDIKAN ISLAM - Siaturrahmah, Anni; Maimun (IAIN Madura, 2024)
This study aims to determine the model of liberal Islamic thought in the novel 'Kemi' by Adian Husaini and to analyze of the model of liberal Islamic thought in the novel